Development of a smart post-hospitalization facility for older people by using domotics, robotics, and automated tele-monitoring - Carlotta Patrone; Alberto Cella; Chiara Martini; Silvia Pericu; Rosetta Femia; Annalisa Barla; Claudia Porfirione; Matteo Puntoni; Nicola Veronese; Francesca Odone; Niccolò Casiddu; Gian Andrea Rollandi; et al. (Geriatric Care, 2019)
Recent studies showed that about the 8% of beds are occupied by patients who experience a delayed hospital discharge (DHD). This is attributed to a delay in the arrangement of home-care assistance or in admission to long-term care facilities. Recently a lot of technologies have been developed to improve caring and monitoring of older people. The aim of this study is to design, implement and test a prototype of a technology based post-hospitalization facility for older people at risk of DHD by using domotics, robotics and wearable sensors for tele-monitoring. A sensorised posthospitalization facility has been built inside the hospital. Thirty-five healthy volunteers aged from 20 to 82 years were recruited. Clinical and functional assessment, i.e. motility index (MI), and human-robot interaction satisfaction were measured. A significant correlation was observed between automatic MI and the Gait Speed, the time sit-to-stand, and the Timed Up and Go test. Domotics, robotics and technology-based telemonitoring may represent a new way to assess patient’s autonomy and functional and clinical conditions in an ecological way, reproducing as much as possible a real life at home.